Mujer y economía. La “narrativa de la crisis” desde la perspectiva de género - Potok, Magda (Studia Romanica Posnaniensia, 2020)
For the last two decades, especially since the 2008 economic crisis, there has been a notable increase in literary works exploring social, political and economic themes in Spain. The growing number of “crisis novels” has reignited the debate about the political role of literature and its ability to challenge and modify existing social models. This article seeks to highlight the female perspective within this discussion. The aim of my analysis of the five novels written by contemporary Spanish female authors (Belén Gopegui, Cristina Fallarás, Cristina Morales, Elvira Navarro and Marta Sanz) and published between 2007 and 2018 is to expose the distinctive female experience as represented in the literature, where it often turns into undermining the system. If women’s literary practice takes the form of political intervention, it is not just because of the collapse of the fundamental trust in the state and its institutions, but mainly due to the shifts in the distribution of the sensible, as we tend to understand the politics of literature after Jacques Rancière.